Long-term evolution of pH and metals (Al, Fe, Mn, U) in pyrite-bearing waste rocks using reactive transport modeling: Dealing with stock and process uncertainties - Sophie Guillon; Pierre L'Hermite; Catherine Beaucaire; Nicolas Seigneur; Martine Leermakers; Benoit Reilé; Vincent Lagneau; Guillaume Kern; Antoine De Amorin; Michael Descostes (Journal of Geochemical Exploration, 2026)

Performance evaluation of the access anti-HCV assay on the DxI 9000 immunoassay analyzer - Benoit Visseaux; Jérémie Gautier; Françoise Le Boulaire; Catherine Coignard; Claire Vincent; Sandrine Gréaume; Isabelle Voisin; Gaiane Demirdjian; Magali Karagueuzian; Juliane Hey; Dan W. Rhodes (Next Research, 2026)

Voacangine/coronaridine hydroxylases catalyze C19-hydroxylation in iboga alkaloid synthesis - Ana Luisa Lopez-Vazquez; Mickael Durand; Caroline Birer-Williams; Elfie Perdereau; Emeline Marais; Thomas Perrot; Audrey Oudin; Arnaud Lanoue; Benoit St-Pierre; Nicolas Papon; Georges Massiot; Chao Sun; et al. (Planta, 2026)

Clinical spectrum of ICU-acquired invasive pulmonary aspergillosis according to SARS-CoV2 infection: a multicenter prospective cohort study - Florian Reizine; Mattéo Mauget; Nicolas Massart; Yannick Fedun; Anaïs Machut; Charles-Hervé Vacheron; Anne Savey; Arnaud Friggeri; Alain Lepape; Melissa Abbes; Abdelkrim Abdelmalek; Francoise Adema; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

The spread of Aoroides longimerus Ren & Zheng, 1996 across the Mediterranean and the Atlantic: genetic diversity, anthropogenic transport, and ecological implications - JOSÉ MANUEL GUERRA-GARCÍA; ANDREA DESIDERATO; SERENA MUCCIOLO; CARLOS NAVARRO-BARRANCO; MACARENA ROS; JASMINE FERRARIO; PAULA MORETTI; AGNESE MARCHINI; NAWFEL MOSBAHI; SOFÍA RUIZ-VELASCO; IGNACIO GESTOSO; PATRÍCIO RAMALHOSA; et al. (Mediterranean Marine Science, 2025)
Accurate knowledge of the global distribution of non-indigenous species (NIS) is essential for understanding their invasion dynamics and for implementing timely management measures. This study reports the first records of the marine amphipod Aoroides longimerus, putatively native to the East Asian coast, in Italy (2018), Spain (2019) and Tunisia (2022) and provides the earliest documented record of the species in its introduced European range (Portugal, 2011). Furthermore, it expands the species’ known distribution in mainland Portugal (including the northernmost record), Macaronesia (with first records in the Canary Islands and Madeira), and confirms its presence along the Atlantic coasts of France and the Netherlands. Aquaculture facilities, particularly those associated with oyster farming, are probably the primary vector of introduction, while recreational boating may have contributed significantly to secondary dispersal. In comparison to other exotic amphipods, A. longimerus remains absent from many marinas, ports and/or aquaculture facilities in the Mediterranean Sea and adjacent regions, such as the Red Sea. This suggests that the species may still be in the early stages of expansion, or that its dispersal ability across marinas and ports is more limited than that of other amphipods. The present study, however, highlights several key ecological traits of A. longimerus: (i) it can survive year-round despite seasonal fluctuations, and reach high local densities, (ii) it exhibits strong colonisation capacity, as shown by its rapid establishment on settlement plates, and (iii) it displays opportunistic feeding behaviour, primarily consuming detritus. These characteristics underscore the importance of continuous surveillance and effective communication with stakeholders to prevent further expansion of this species.

Corrigendum to “Oak regeneration facing deer browsing: Can competition between saplings offset the diversion effect? A simulation experiment” [Ecological Modelling 489 (2024) 110608] - Julien Barrere; Gauthier Ligot; Vincent Boulanger; Catherine Collet; Benoit Courbaud; François de Coligny; Anders Mårell; Sonia Saïd; Philippe Balandier (Ecological Modelling, 2025)

Late 21st‐Century Climate and Land Use Driven Loss of Plant Diversity in African Mountains - João de Deus Vidal Junior; Alexandre Antonelli; Clinton Carbutt; Vincent Ralph Clark; Tobias Fremout; Christopher Chapano; Inês Chelene; David Chuba; Tadesse Woldemariam Gole; Clayton Langa; Benoit Loeuille; Ermias Lulekal Molla; et al. (Global Change Biology, 2025)
With the 1.5°C–5°C increase in global temperature projected for this century, many plant species are expected to shift their distribution ranges to track their environmental requirements. Across several mountain regions, responses to climate change like upslope shifts may result in accelerated rates of species turnover, species richness increases in upper montane belts, and amplified habitat losses. Yet, evidence of how such processes may influence plant diversity in Africa is still scarce. Here, using a species distribution modeling approach, we quantify and map how different scenarios of climatic and land‐use changes may affect plant species ranges in African mountains. Using individually tuned models and dispersal buffers, we compared distribution losses and potential expansion through dispersal across 607 vascular plant species under three shared socioeconomic pathways for the end of the century. Our projections indicate that keeping warming under 2°C until 2100 under a sustainability scenario (SSP1.26), almost half (49.3%) of the species would experience a contraction in suitable areas, compared to 71%–75.6% in case these targets are not met (SSP3.70 and SSP5.85). Among these losses, mean contractions between 19% and 50.4% are predicted depending on the scenario. We project rates of upslope shifts that may be up to three times higher than the global calculated average. Contractions will be higher for species occurring at upper elevations, and trees and shrubs will show lower declines. Our findings align with previously reported trends of upslope shifts of species distributions but suggest that accelerated rates of change may limit the capacity of some species to track their niche based solely on their natural dispersal capacity. This implies that further efforts to improve habitat connectivity, restoration, and assisted migration may be necessary.

Dynamics of tephra fallout and column collapse during Plinian eruptions of Mt. Pelée volcano (Lesser Antilles): The 2.5 ka cal BCE P5 eruption - Guillaume Carazzo; Audrey Michaud-Dubuy; Vincent Bellier; Benoit Vittecoq (Journal of Volcanology and Geothermal Research, 2025)

Life history stage effects on alert and flight initiation distances in king penguins (Aptenodytes patagonicus) - Tracey L. Hammer; Pierre Bize; Benoit Gineste; Jean-Patrice Robin; René Groscolas; Vincent A. Viblanc (Behavioural Processes, 2025)

Biodegradable twine for trawl fishing: Seawater ageing and net modelling - Louis Le Gué; Mael Arhant; Peter Davies; Benoit Vincent; Erwan Tanguy (Marine Pollution Bulletin, 2025)

Venom peptides as promising tools for lung cancer diagnosis - Romain Baudat; Evelyne Benoit; Pascal Kessler; Benoit Jego; Mathilde Keck; Vincent Thomas De Montpreville; Charles Truillet; Denis Servent (Toxicon, 2024)

Smart soils track the formation of pH gradients across the rhizosphere - Daniel Patko; Qizhi Yang; Yangminghao Liu; Panagiotis Falireas; Benoit Briou; Bhausaheb V. Tawade; Timothy S. George; Tim J. Daniell; Michael P. MacDonald; Vincent Ladmiral; Bruno Ameduri; Lionel X. Dupuy (Plant and Soil, 2024)
Aims Our understanding of the rhizosphere is limited by the lack of techniques for in situ live microscopy. Current techniques are either destructive or unsuitable for observing chemical changes within the pore space. To address this limitation, we have developed artificial substrates, termed smart soils, that enable the acquisition and 3D reconstruction of chemical sensors attached to soil particles. Methods The transparency of smart soils was achieved using polymer particles with refractive index matching that of water. The surface of the particles was modified both to retain water and act as a local sensor to report on pore space pH via fluorescence emissions. Multispectral signals were acquired from the particles using a light sheet microscope, and machine learning algorithms predicted the changes and spatial distribution in pH at the surface of the smart soil particles. Results The technique was able to predict pH live and in situ within ± 0.5 units of the true pH value. pH distribution could be reconstructed across a volume of several cubic centimetres around plant roots at 10 μm resolution. Using smart soils of different composition, we revealed how root exudation and pore structure create variability in chemical properties. Conclusion Smart soils captured the pH gradients forming around a growing plant root. Future developments of the technology could include the fine tuning of soil physicochemical properties, the addition of chemical sensors and improved data processing. Hence, this technology could play a critical role in advancing our understanding of complex rhizosphere processes.

Effects of temperature on the performance of Palaemon serratus (Pennant, 1777) larvae from winter and summer laying - Jean-Baptiste Baudet; Benoit Xuereb; Michael Danger; Vincent Felten; Aurélie Duflot; Agnès Poret; Frank Le Foll; Romain Coulaud (Journal of Experimental Marine Biology and Ecology, 2024)

Persistent headaches one year after bacterial meningitis: prevalence, determinants and impact on quality of life - Rémi Nguyen Van; Sarah Tubiana; Thomas De Broucker; Joseph Cédric; Carine Roy; Marie-Caroline Meyohas; Thierry Prazuck; Catherine Chirouze; Bruno Hoen; Xavier Duval; Matthieu Revest; Bruno Mourvillier; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2023)

Technological innovations to reduce the impact of bottom gears on the seabed - Antonello Sala; Jochen Depestele; Aysun Gümüş; Pascal Laffargue; J. Rasmus Nielsen; Hans Polet; Chris J. Smith; Mustafa Zengin; Francois Bastardie; Ole R. Eigaard; Katell G. Hamon; Frank Jensen; et al. (Marine Policy, 2023)

Combined impact of no-tillage and cover crops on soil carbon stocks and fluxes in maize crops - Nicolas L. Breil; Thierry Lamaze; Vincent Bustillo; Claire-Emmanuelle Marcato-Romain; Benoit Coudert; Solen Queguiner; Nathalie Jarosz-Pellé (Soil and Tillage Research, 2023)

Mitigating plastic pollution at sea: Natural seawater degradation of a sustainable PBS/PBAT marine rope - Louis Le Gué; Peter Davies; Mael Arhant; Benoit Vincent; Erwan Tanguy (Marine Pollution Bulletin, 2023)

The great shift: The non-indigenous species Ammonia confertitesta (Foraminifera, Rhizaria) outcompetes indigenous Ammonia species in the Gironde estuary (France) - Jean-Charles Pavard; Julien Richirt; Laurent Seuront; Hugues Blanchet; Marie P.A. Fouet; Suzie Humbert; Benoit Gouillieux; Gwendoline Duong; Vincent M.P. Bouchet (Estuarine, Coastal and Shelf Science, 2023)

Disentangling the “many-eyes”, “dilution effect”, “selfish herd”, and “distracted prey” hypotheses in shaping alert and flight initiation distance in a colonial seabird - Tracey L. Hammer; Pierre Bize; Benoit Gineste; Jean-Patrice Robin; René Groscolas; Vincent A. Viblanc (Behavioural Processes, 2023)

Montagne Pelée volcano (Martinique, in the French Lesser Antilles) hydrogeological system revealed by high-resolution helicopter-borne electromagnetic imagery - Benoit Vittecoq; Pierre-Alexandre Reninger; Vincent Bellier; Anne-Lise Taïlamé; Laureen Nacimento; Emile Gros; Sophie Violette (Hydrogeology Journal, 2023)
Montagne Pelée, on the French island of Martinique, eastern Caribbean Sea, has been one of the deadliest volcanoes in the world, with 30,000 victims following the 1902 eruption. Thousands of people still live nearby, and this volcano is a strategic “water tank” for Martinique Island, providing 40% of the island’s water supply. This research aimed to better understand its hydrogeological functioning and the relationship with its complex volcanological evolution, taking advantage of a high-resolution helicopter-borne geophysical survey correlated with hydrogeological data from the boreholes and springs databases. Electromagnetic data, correlated with hydrogeological data, allowed for the identification of unsaturated zones, aquifers, and seawater intrusions, as well as the main geological units. In addition, data synthesised from pumping tests revealed that the older the unconsolidated pyroclastic deposits, the lower their hydraulic conductivity. The structural asymmetry between the northeastern and southwestern volcano flanks impacts its hydrogeological functioning. Consequently, the Montagne Pelée hydrogeological conceptual model is marked by several distinguishable aquifers. The upper perched aquifer within recent lava domes is directly involved in, and impacted by, phreatic eruptions, and it supports low flowrate springs. The remaining effective rainfall infiltrates to depth and recharges the hydrothermal system through vertical fractures. The other aquifers are categorized into three groups: northeastern, southeastern and southwestern flank aquifers. This research is a new step toward a better understanding of the Lesser Antilles volcanoes and more broadly of the central and proximal parts of the andesitic active volcanoes.

Metamorphic reactions and their implication for the fluid budget in metapelites at seismogenic depths in subduction zones - Kristijan Rajič; Hugues Raimbourg; Catherine Lerouge; Vincent Famin; Benoit Dubacq; Aurélien Canizarés; Ida Di Carlo; Nicolas Maubec (Tectonophysics, 2023)

Spatial localization of monoterpenoid indole alkaloids in Rauvolfia tetraphylla by high resolution mass spectrometry imaging - Marcus Daniel Brandbjerg Bohn Lorensen; Nanna Bjarnholt; Benoit St-Pierre; Sarah Heinicke; Vincent Courdavault; Sarah O'Connor; Christian Janfelt (Phytochemistry, 2023)

Data quality control considerations in multivariate environmental monitoring: experience of the French coastal network SOMLIT - Elsa Breton; Nicolas Savoye; Peggy Rimmelin-Maury; Benoit Sautour; Eric Goberville; Arnaud Lheureux; Thierry Cariou; Sophie Ferreira; Hélène Agogué; Samir Alliouane; Fabien Aubert; Sébastien Aubin; et al. (Frontiers in Marine Science, 2023)
Introduction While crucial to ensuring the production of accurate and high-quality data—and to avoid erroneous conclusions—data quality control (QC) in environmental monitoring datasets is still poorly documented. Methods With a focus on annual inter-laboratory comparison (ILC) exercises performed in the context of the French coastal monitoring SOMLIT network, we share here a pragmatic approach to QC, which allows the calculation of systematic and random errors, measurement uncertainty, and individual performance. After an overview of the different QC actions applied to fulfill requirements for quality and competence, we report equipment, accommodation, design of the ILC exercises, and statistical methodology specially adapted to small environmental networks (<20 laboratories) and multivariate datasets. Finally, the expanded uncertainty of measurement for 20 environmental variables routinely measured by SOMLIT from discrete sampling—including Essential Ocean Variables—is provided. Results, Discussion, Conclusion The examination of the temporal variations (2001–2021) in the repeatability, reproducibility, and trueness of the SOMLIT network over time confirms the essential role of ILC exercises as a tool for the continuous improvement of data quality in environmental monitoring datasets.

A research-action process to implement priority areas for alien plant clearing on Reunion Island - Pauline Fenouillas; Claudine Ah-Peng; Elise Amy; Isabelle Bracco; Laurent Calichiama; Emilie Cazal; Mélodie Gosset; Florent Ingrassia; Christophe Lavergne; Benoit Lequette; Jean-Cyrille Notter; Jean-Marie Pausé; et al. (Biological Invasions, 2023)

Trace elements, dioxins and PCBs in different fish species and marine regions: Importance of the taxon and regional features - Aourell Mauffret; Tiphaine Chouvelon; Nathalie Wessel; Pierre Cresson; Daniela Bănaru; Jérôme Baudrier; Paco Bustamante; Rachida Chekri; Petru Jitaru; François Le Loc'h; Benoit Mialet; Vincent Vaccher; et al. (Environmental Research, 2023)

Water table depth modulates productivity and biomass across Amazonian forests - Thaiane R. Sousa; Juliana Schietti; Igor O. Ribeiro; Thaise Emílio; Rafael Herrera Fernández; Hans ter Steege; Carolina V. Castilho; Adriane Esquivel‐Muelbert; Timothy Baker; Aline Pontes‐Lopes; Camila V. J. Silva; Juliana M. Silveira; et al. (Global Ecology and Biogeography, 2022)
Aim Water availability is the major driver of tropical forest structure and dynamics. Most research has focused on the impacts of climatic water availability, whereas remarkably little is known about the influence of water table depth and excess soil water on forest processes. Nevertheless, given that plants take up water from the soil, the impacts of climatic water supply on plants are likely to be modulated by soil water conditions. Location Lowland Amazonian forests. Time period 1971–2019. Methods We used 344 long‐term inventory plots distributed across Amazonia to analyse the effects of long‐term climatic and edaphic water supply on forest functioning. We modelled forest structure and dynamics as a function of climatic, soil‐water and edaphic properties. Results Water supplied by both precipitation and groundwater affects forest structure and dynamics, but in different ways. Forests with a shallow water table (depth Main conclusions We show that the two extremes of water availability (excess and deficit) both reduce productivity in Amazon upland ( terra‐firme ) forests. Biomass and productivity across Amazonia respond not simply to regional climate, but rather to its interaction with water table conditions, exhibiting high local differentiation. Our study disentangles the relative contribution of those factors, helping to improve understanding of the functioning of tropical ecosystems and how they are likely to respond to climate change.

Changes in cardiac function following a speed ascent to the top of Europe at 4808 m - Benoit Champigneulle; Stéphane Doutreleau; Sébastien Baillieul; Julien Vincent Brugniaux; Paul Robach; Pierre Bouzat; Samuel Verges (European Journal of Applied Physiology, 2022)

Effect of a speed ascent to the top of Europe on cognitive function in elite climbers - Benoit Champigneulle; Karen Davranche; Julien Vincent Brugniaux; Sébastien Baillieul; Thibault Gajdos; Stéphane Doutreleau; Paul Robach; Pierre Bouzat; Samuel Verges (European Journal of Applied Physiology, 2022)

The climatic debt is growing in the understorey of temperate forests: Stand characteristics matter - Benoit Richard; Jean‐Luc Dupouey; Emmanuel Corcket; Didier Alard; Frédéric Archaux; Michaël Aubert; Vincent Boulanger; François Gillet; Estelle Langlois; Sébastien Macé; Pierre Montpied; Thérèse Beaufils; et al. (Global Ecology and Biogeography, 2021)
Aim Climate warming reshuffles biological assemblages towards less cold‐adapted but more warm‐adapted species, a process coined thermophilization. However, the velocity at which this process is happening generally lags behind the velocity of climate change, generating a climatic debt the temporal dynamics of which remain misunderstood. Relying on high‐resolution time series of vegetation data from a long‐term monitoring network of permanent forest plots, we aim at quantifying the temporal dynamics – up to a yearly resolution – of the climatic debt in the understorey of temperate forests before identifying the key determinants that modulate it. Location France. Time period 1995–2017. Taxa studied Vascular plants. Methods We used the community temperature index (CTI) to produce a time series of understorey plant community thermophilization, which we subsequently compared to a time series of mean annual temperature changes over the same period and for the same sites. The direction and magnitude of the difference (i.e., the climatic debt) was finally analysed using linear mixed‐effect models to assess the relative contributions of abiotic and biotic determinants, including forest stand characteristics. Results We found a significant increase in CTI values over time (0.08–0.09 °C/decade), whereas the velocity of mean annual temperature changes was three times higher over the same period (0.22–0.28 °C/decade). Hence, the climatic debt increased over time and was greater in forest stands with higher basal area or older trees as well as under warmer macroclimate. By contrast, a greater frequency of anthropogenic disturbances decreased the climatic debt, while natural disturbances and herbivory had no impact. Conclusions Although often overlooked in understanding the climatic debt of forest biodiversity, changes in forest stand characteristics may modulate the climatic debt by locally modifying microclimatic conditions. Notably, the buffering effect of the upper canopy layer implies microclimate dynamics that may provide more time for understorey plant communities to locally adapt.

Giant subaqueous carbonate dunes: a revised interpretation of large-scale oo-bioclastic clinoforms in the middle Jurassic of the Paris Basin and its implications - Benoit Vincent; Benjamin Brigaud; Hadrien Thomas; Fabrice Gaumet (Facies, 2021)

The Evolution of the Maxillary Canal in Probainognathia (Cynodontia, Synapsida): Reassessment of the Homology of the Infraorbital Foramen in Mammalian Ancestors - Julien Benoit; Irina Ruf; Juri A. Miyamae; Vincent Fernandez; Pablo Gusmão Rodrigues; Bruce S. Rubidge (Journal of Mammalian Evolution, 2020)

Complementarity of grasslands and cereal fields ensures carabid regional diversity in French farmlands - Damien Massaloux; Benoit Sarrazin; Anthony Roume; Vincent Tolon; Alexander Wezel (Biodiversity and Conservation, 2020)

Potential adaptive divergence between subspecies and populations of snapdragon plants inferred from Q ST – F ST comparisons - Sara Marin; Anaïs Gibert; Juliette Archambeau; Vincent Bonhomme; Mylène Lascoste; Benoit Pujol (Molecular Ecology, 2020)
Phenotypic divergence among natural populations can be explained by natural selection or by neutral processes such as drift. Many examples in the literature compare putatively neutral ( F ST ) and quantitative genetic ( Q ST ) differentiation in multiple populations to assess their evolutionary signature and identify candidate traits involved with local adaptation. Investigating these signatures in closely related or recently diversified species has the potential to shed light on the divergence processes acting at the interspecific level. Here, we conducted this comparison in two subspecies of snapdragon plants (eight populations of Antirrhinum majus pseudomajus and five populations of A. m. striatum ) in a common garden experiment. We also tested whether altitude was involved with population phenotypic divergence. Our results identified candidate phenological and morphological traits involved with local adaptation. Most of these traits were identified in one subspecies but not the other. Phenotypic divergence increased with altitude for a few biomass‐related traits, but only in A. m. striatum . These traits therefore potentially reflect A. m. striatum adaptation to altitude. Our findings imply that adaptive processes potentially differ at the scale of A. majus subspecies.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

RECOTOX, a French initiative in ecotoxicology-toxicology to monitor, understand and mitigate the ecotoxicological impacts of pollutants in socioagroecosystems - Christian Mougin; Véronique Gouy; Vincent Bretagnolle; Julie Berthou; Patrick Andrieux; Patrick Ansart; Marc Benoit; Michaël Coeurdassier; Irina Comte; Cécile Dagès; Laurence Denaix; Sylvie Dousset; et al. (Environmental Science and Pollution Research, 2018)

Pan‐tropical prediction of forest structure from the largest trees - Jean‐François Bastin; Ervan Rutishauser; James R. Kellner; Sassan Saatchi; Raphael Pélissier; Bruno Hérault; Ferry Slik; Jan Bogaert; Charles De Cannière; Andrew R. Marshall; John Poulsen; Patricia Alvarez‐Loyayza; et al. (Global Ecology and Biogeography, 2018)
Aim Large tropical trees form the interface between ground and airborne observations, offering a unique opportunity to capture forest properties remotely and to investigate their variations on broad scales. However, despite rapid development of metrics to characterize the forest canopy from remotely sensed data, a gap remains between aerial and field inventories. To close this gap, we propose a new pan‐tropical model to predict plot‐level forest structure properties and biomass from only the largest trees. Location Pan‐tropical. Time period Early 21st century. Major taxa studied Woody plants. Methods Using a dataset of 867 plots distributed among 118 sites across the tropics, we tested the prediction of the quadratic mean diameter, basal area, Lorey's height, community wood density and aboveground biomass (AGB) from the i th largest trees. Results Measuring the largest trees in tropical forests enables unbiased predictions of plot‐ and site‐level forest structure. The 20 largest trees per hectare predicted quadratic mean diameter, basal area, Lorey's height, community wood density and AGB with 12, 16, 4, 4 and 17.7% of relative error, respectively. Most of the remaining error in biomass prediction is driven by differences in the proportion of total biomass held in medium‐sized trees (50–70 cm diameter at breast height), which shows some continental dependency, with American tropical forests presenting the highest proportion of total biomass in these intermediate‐diameter classes relative to other continents. Main conclusions Our approach provides new information on tropical forest structure and can be used to generate accurate field estimates of tropical forest carbon stocks to support the calibration and validation of current and forthcoming space missions. It will reduce the cost of field inventories and contribute to scientific understanding of tropical forest ecosystems and response to climate change.

One-Single Extraction Procedure for the Simultaneous Determination of a Wide Range of Polar and Nonpolar Organic Contaminants in Seawater - Vincent Fauvelle; Javier Castro-Jiménez; Natascha Schmidt; Benoit Carlez; Christos Panagiotopoulos; Richard Sempéré (Frontiers in Marine Science, 2018)

Response to Editor to the comment by Schipper & Smith to our paper entitled “Continuous soil carbon storage of old permanent pastures in Amazonia” - Sébastien Fontaine; Clément Stahl; Katja Klumpp; Catherine Picon‐Cochard; Marcia M. Grise; Camille Dezécache; Lise Ponchant; Vincent Freycon; Lilian Blanc; Damien Bonal; Benoit Burban; Jean‐François Soussana; et al. (Global Change Biology, 2018)

The mystery of a missing bone: revealing the orbitosphenoid in basal Epicynodontia (Cynodontia, Therapsida) through computed tomography - Julien Benoit; Sandra C. Jasinoski; Vincent Fernandez; Fernando Abdala (The Science of Nature, 2017)

Continuous soil carbon storage of old permanent pastures in Amazonia - Clément Stahl; Sébastien Fontaine; Katja Klumpp; Catherine Picon‐Cochard; Marcia Mascarenhas Grise; Camille Dezécache; Lise Ponchant; Vincent Freycon; Lilian Blanc; Damien Bonal; Benoit Burban; Jean‐François Soussana; et al. (Global Change Biology, 2017)
Amazonian forests continuously accumulate carbon (C) in biomass and in soil, representing a carbon sink of 0.42–0.65 GtC yr −1 . In recent decades, more than 15% of Amazonian forests have been converted into pastures, resulting in net C emissions (~200 tC ha −1 ) due to biomass burning and litter mineralization in the first years after deforestation. However, little is known about the capacity of tropical pastures to restore a C sink. Our study shows in French Amazonia that the C storage observed in native forest can be partly restored in old (≥24 year) tropical pastures managed with a low stocking rate (±1 LSU ha −1 ) and without the use of fire since their establishment. A unique combination of a large chronosequence study and eddy covariance measurements showed that pastures stored between −1.27 ± 0.37 and −5.31 ± 2.08 tC ha −1 yr −1 while the nearby native forest stored −3.31 ± 0.44 tC ha −1 yr −1 . This carbon is mainly sequestered in the humus of deep soil layers (20–100 cm), whereas no C storage was observed in the 0‐ to 20‐cm layer. C storage in C4 tropical pasture is associated with the installation and development of C3 species, which increase either the input of N to the ecosystem or the C:N ratio of soil organic matter. Efforts to curb deforestation remain an obvious priority to preserve forest C stocks and biodiversity. However, our results show that if sustainable management is applied in tropical pastures coming from deforestation (avoiding fires and overgrazing, using a grazing rotation plan and a mixture of C3 and C4 species), they can ensure a continuous C storage, thereby adding to the current C sink of Amazonian forests.

Virus-induced gene silencing in Rauwolfia species - Cyrielle Corbin; Florent Lafontaine; Liuda Johana Sepúlveda; Ines Carqueijeiro; Martine Courtois; Arnaud Lanoue; Thomas Dugé de Bernonville; Sébastien Besseau; Gaëlle Glévarec; Nicolas Papon; Lucia Atehortúa; Nathalie Giglioli-Guivarc’h; et al. (Protoplasma, 2017)

Virus-induced gene silencing of the two squalene synthase isoforms of apple tree (Malus × domestica L.) negatively impacts phytosterol biosynthesis, plastid pigmentation and leaf growth - Sandra M. Navarro Gallón; Carolina Elejalde-Palmett; Dimitri Daudu; Franziska Liesecke; Frédéric Jullien; Nicolas Papon; Thomas Dugé de Bernonville; Vincent Courdavault; Arnaud Lanoue; Audrey Oudin; Gaëlle Glévarec; Olivier Pichon; et al. (Planta, 2017)

Influence of bottom trawling on sediment resuspension in the ‘Grande-Vasière’ area (Bay of Biscay, France) - Baptiste Mengual; Florence Cayocca; Pierre Le Hir; Robin Draye; Pascal Laffargue; Benoit Vincent; Thierry Garlan (Ocean Dynamics, 2016)

Integration of global fossil and modern biodiversity data reveals dynamism and stasis in ant macroecological patterns - Benoit Guénard; Vincent Perrichot; Evan P. Economo (Journal of Biogeography, 2015)
Aim We investigate the dynamics of ant biodiversity patterns and community structure from the Eocene until the present. Our goal is to empirically test hypotheses regarding the similarities in composition and structure of fossil and modern ant faunas to understand the historical processes influencing modern global biodiversity patterns. Location Global. Methods We integrated two recently developed databases of the geographical distributions of fossil and modern ant genera and analysed the evolution of diversity and composition since the Eocene, c . 55 Ma. We assembled a third new database on community structure of ants, and used it to compare community structure of fossil assemblages with modern communities in different bioregions. Results The analyses of generic composition and community structure were congruent, supporting a strong affinity between the Western Palaearctic ant fauna and modern Indomalayan and Australasian assemblages, and of a widespread Holarctic ant palaeofauna, and affinity between fossil Caribbean and modern Neotropical faunas. In addition, neither generic composition nor community structure of fossil assemblages showed evidence of taphonomic bias towards arboreal taxa. Main Conclusions The aggregated fossil record reveals the dynamic nature of macroecological patterns in ant biodiversity during the Cenozoic, with continental‐scale generic extinctions common and important in shaping modern ant assemblages. Our results suggest major compositional changes for the Western Palaearctic bioregion and the Caribbean bioregions. The ant palaeofauna of the Western Palaearctic bioregion was then very similar in composition and structure to the one observed now in the Indomalayan bioregion, supporting the notion that modern‐day ‘tropical’ biomes were historically much more widespread, while temperate biotas are more recently evolved. Our results underscore the importance of a palaeogeographical perspective in understanding modern‐day macroecological patterns.

Stress hormones in relation to breeding status and territory location in colonial king penguin: a role for social density? - Vincent A. Viblanc; Benoit Gineste; Antoine Stier; Jean-Patrice Robin; René Groscolas (Oecologia, 2014)

A single gene encodes isopentenyl diphosphate isomerase isoforms targeted to plastids, mitochondria and peroxisomes in Catharanthus roseus - Grégory Guirimand; Anthony Guihur; Michael A. Phillips; Audrey Oudin; Gaëlle Glévarec; Céline Melin; Nicolas Papon; Marc Clastre; Benoit St-Pierre; Manuel Rodríguez-Concepción; Vincent Burlat; Vincent Courdavault (Plant Molecular Biology, 2012)

Molecular cloning and functional characterization of Catharanthus roseus hydroxymethylbutenyl 4-diphosphate synthase gene promoter from the methyl erythritol phosphate pathway - Olivia Ginis; Vincent Courdavault; Céline Melin; Arnaud Lanoue; Nathalie Giglioli-Guivarc’h; Benoit St-Pierre; Martine Courtois; Audrey Oudin (Molecular Biology Reports, 2012)

Automatic unmixing of MODIS multi-temporal data for inter-annual monitoring of land use at a regional scale (Tensift, Morocco) - Iskander Benhadj; Benoit Duchemin; Philippe Maisongrande; Vincent Simonneaux; Saïd Khabba; Abdelghani Chehbouni (International Journal of Remote Sensing, 2012)

The complete phylogeny of Pseudobulweria, the most endangered seabird genus: systematics, species status and conservation implications - Benoit Gangloff; Hadoram Shirihai; Dick Watling; Corinne Cruaud; Arnaud Couloux; Annie Tillier; Eric Pasquet; Vincent Bretagnolle (Conservation Genetics, 2012)

Pelagic food web patterns: do they modulate virus and nanoflagellate effects on picoplankton during the phytoplankton spring bloom? - Pascaline Ory; Hans J. Hartmann; Florence Jude; Christine Dupuy; Yolanda Del Amo; Philippe Catala; Françoise Mornet; Valérie Huet; Benoit Jan; Dorothée Vincent; Benoit Sautour; Hélène Montanié (Environmental Microbiology, 2010)
Summary As agents of mortality, viruses and nanoflagellates impact on picoplankton populations. We examined the differences in interactions between these compartments in two French Atlantic bays. Microbes, considered here as central actors of the planktonic food web, were first monitored seasonally in Arcachon (2005) and Marennes‐Oléron (2006) bays. Their dynamics were evaluated to categorize trophic periods using the models of Legendre and Rassoulzadegan as a reference framework. Microbial interactions were then compared through 48 h batch culture experiments performed during the phytoplankton spring bloom, identified as herbivorous in Marennes and multivorous in Arcachon. Marennes was spatially homogeneous compared with Arcachon. The former was potentially more productive, featuring a large number of heterotrophic pathways, while autotrophic mechanisms dominated in Arcachon. A link was found between viruses and phytoplankton in Marennes, suggesting a role of virus in the regulation of autotroph biomass. Moreover, the virus–bacteria relation was weaker in Marennes, with a bacterial lysis potential of 2.6% compared with 39% in Arcachon. The batch experiments (based on size‐fractionation and viral enrichment) revealed different microbial interactions that corresponded to the spring‐bloom trophic interactions in each bay. In Arcachon, where there is a multivorous web, flagellate predation and viral lysis acted in an opposite way on picophytoplankton. When together they both reduced viral production. Conversely, in Marennes (herbivorous web), flagellates and viruses together increased viral production. Differences in the composition of the bacterial community composition explained the combined flagellate‐virus effects on viral production in the two bays.

A roadmap for a dedicated Earth Science Grid platform - Roberto Cossu; Monique Petitdidier; Julian Linford; Vincent Badoux; Luigi Fusco; Benoit Gotab; Ladislav Hluchy; Giuditta Lecca; Fabrizio Murgia; Camiel Plevier; Philippe Renard; Horst Schwichtenberg; et al. (Earth Science Informatics, 2010)

Optimization of the transient transformation of Catharanthus roseus cells by particle bombardment and its application to the subcellular localization of hydroxymethylbutenyl 4-diphosphate synthase and geraniol 10-hydroxylase - Grégory Guirimand; Vincent Burlat; Audrey Oudin; Arnaud Lanoue; Benoit St-Pierre; Vincent Courdavault (Plant Cell Reports, 2009)

Proteins prenylated by type I protein geranylgeranyltransferase act positively on the jasmonate signalling pathway triggering the biosynthesis of monoterpene indole alkaloids in Catharanthus roseus - Vincent Courdavault; Vincent Burlat; Benoit St-Pierre; Nathalie Giglioli-Guivarc’h (Plant Cell Reports, 2009)

Molecular characterisation of a cypovirus isolated from the western spruce budworm Choristoneura occidentalis - Robert I. Graham; Benoit Morin; Renée Lapointe; Vincent G. Nealis; Christopher J. Lucarotti (Archives of Virology, 2008)

Spatial distribution and hormonal regulation of gene products from methyl erythritol phosphate and monoterpene-secoiridoid pathways in Catharanthus roseus - Audrey Oudin; Samira Mahroug; Vincent Courdavault; Nadège Hervouet; Charles Zelwer; Manuel Rodríguez-Concepción; Benoit St-Pierre; Vincent Burlat (Plant Molecular Biology, 2007)

Cellular and sub-cellular organisation of the monoterpenoid indole alkaloid pathway in Catharanthus roseus - Samira Mahroug; Vincent Burlat; Benoit St-Pierre (Phytochemistry Reviews, 2007)

Epidermis is a pivotal site of at least four secondary metabolic pathways in Catharanthus roseus aerial organs - Samira Mahroug; Vincent Courdavault; Martine Thiersault; Benoit St-Pierre; Vincent Burlat (Planta, 2006)

Sedimentology and trace element geochemistry of shallow-marine carbonates: an approach to paleoenvironmental analysis along the Pagny-sur-Meuse Section (Upper Jurassic, France) - Benoit Vincent; Claire Rambeau; Laurent Emmanuel; Jean-Paul Loreau (Facies, 2006)

CaaX-prenyltransferases are essential for expression of genes involvedin the early stages of monoterpenoid biosynthetic pathwayin Catharanthus roseus cells - Vincent Courdavault; Martine Thiersault; Martine Courtois; Pascal Gantet; Audrey Oudin; Pierre Doireau; Benoit St-Pierre; Nathalie Giglioli-Guivarc’h (Plant Molecular Biology, 2005)

Usefulness of AFLP markers to estimate varietal homogeneity of rapeseed inbred line varieties in the context of plant registration and protection - Vincent Lombard; Benoit Tireau; Françoise Blouet; David Zhang; Claire P. Baril (Euphytica, 2002)